Esto Significa Aquello, Formas De Significacion Urbana En Ciudad Juárez (México) Y Armenia (Colombia) (2013)
Formas de Significación Urbana is a research that intended to analyze the different uses of the language in the city, and how they helped to create new meanings and imaginary forms; reason why, this chapter was devoted to the uses of the language in the city of Armenia. The mass media being one of the most representative voices in city constitute, in an indirect way, the imaginary of it, so taking into consideration this phenomenon, were analyzed the most widely circulated media such as written press and radio in the city of Armenia. As a result, it determined that the above mentioned means appeal to the immediacy of the information, and to the "chiva informativa" laying emphasis just only on the news of judicial processes or political injunction, creating an imaginary of dangerous city in the process of growth being divided by partisan sectors. In the same way, contrasting the information that the local media offered with the daily conversations of the citizens of Armenia who were analyzed, one concluded that for the Armenians this city is nice, pleasant and calm which makes it a suitable place to live and settle down with the family.